Protective effects of anthocyanins from bilberry extract in rats exposed to nephrotoxic effects of carbon tetrachloride. (1st May 2019) - Popović, Dejan; Kocić, Gordana; Katić, Vuka; Jović, Zorica; Zarubica, Aleksandra; Janković Veličković, Ljubinka; Nikolić, Valentina; Jović, Andrija; Kundalić, Braca; Rakić, Violeta; Ulrih, Nataša Poklar; Skrt, Mihaela; et al.
Abstract: This study examined the nephroprotective effects of 15 different anthocyanins from the bilberry extract on the acute kidney injury caused by CCl4 . The acute nephrotoxicity in rats was induced 24 h after the treatment with a single dose of CCl4 (3 mL/kg, i.p.).The nephroprotective effects of the anthocyanins were examined in the animals that had been given the bilberry extract in a single dose of 200 mg of anthocyanins/kg daily, 7 days orally, while on the seventh day, 3 h after the last dose of anthocyanins, the animals received a single dose of CCl4 (3 mL/kg, i.p.) and were sacrificed 24 h later. When the nephrotoxicant alone was administered, it resulted in a substantial increase of the pro-oxidative (TBARS, CD, H2 O2, XO, and GSSG) and pro-inflammatory markers (TNF-α, NO, and MPO), as well as a noticeable reduction of the antioxidant enzymes (CAT, SOD, POD, GPx, GST, GR) and GSH when compared to the results of the control group. Moreover, the application of CCl4 significantly influenced a reduction of the renal function, as well as an increase in the sensitive and specific injury indicators of the kidney epithelial cells (β2 -microglobulin, NGAL, KIM1/TIM1) in the serum and urine of rats. The pretreatment of the animals poisoned with CCl4 with the anthocyanins from the bilberry extract led to a noticeable reduction in the pro-oxidative and pro-inflammatory markers with reduced consumption of the antioxidant defence kidney capacity, compared to the animals exposed to CCl4 alone. Anthocyanins have been protective for the kidney parenchyma, with an apparent absence of the tubular and periglomerular necrosis, severe degenerative changes, inflammatory mononuclear infiltrates and dilatation of proximal and distal tubules, in contrast to the CCl4 -intoxicated animals. The nephroprotective effects of anthocyanins can be explained by strong antioxidant and anti-inflammatory effects achieved through the stabilization and neutralization of highly reactive and unstable toxic CCl4 metabolites. Graphical abstract: Image 1 Highlights: Anthocyanins reduce the acute nephrotoxic damage caused by CCl4 . Anthocyanins have an antioxidant and anti-inflammatory activity. Anthocyanins decrease the NGAL and KIM1/TIM biomarkers. Anthocyanins prevent necrosis in the tubular cells.